The early Colombian labor movement : artisans and politics in Bogotá, 1832-1919 - Sowell, David, 1952- (Temple University Press, 1992)
"In this book, David Sowell traces the history of artisan labor organizations in Bogota and examines long-term political activity of Colombian artisans in the century after independence. Relying on contemporary newspapers, political handouts, broadsides, and public petitions, Sowell describes and analyzes the economic, social, and political history of the capital's artisan class, a middling social sector with very significant social and political strengths. Latin American labor history has heretofore focused almost exclusively on twentieth-century industrial or agrarian laborers. This is the first study in English of nineteenth-century Latin American artisans and one of the few treatments that spans the whole of nineteenth-century Colombian history."--BOOK JACKET. "The rise and subsequent decline of artisan class political activity coincided with Colombia's integration into the world market. Initially petitioning for tariff protection, Bogota's craftsmen in time mobilized to address numerous issues, including industrial education, internal trade order, credit, and better health and educational facilities. The artisan class was a sizeable share of the urban electorate and, at the beginning of this period, was essentially cohesive. Sowell traces the transformation of Colombia's economy and the (mainly negative) effects its evolution had on bogotano artisans. By the end of the nineteenth century, the fragmentation of the artisan class had destroyed their broad mobilizations. No longer leaders of the Colombian labor movement, the artisans were replaced by laborers associated with industrial production, transportation systems, and the production of coffee."--BOOK JACKET. "The study of artisan-based labor activity illuminates the foundations of contemporary Latin American societies. Sowell's examination of the political expression of artisan class interests and the social and political variables that affected those interests sheds light on the subsequent industrial development in Colombia as well as on the "modern" period of Latin American history."--Jacket